VD_FINDINFO HC / 2013 / 658 vom 20. September 2013 - VD Tribunal cantonal (2013)
ACTION EN CESSATION DE TROUBLE, SERVITUDE, DANGEREN GÉNÉRAL, ILLICÉITÉ, MESURE PROVISIONNELLE | 641 CC, 730 CC, 737 CC, 741 CC